KAJIAN PENGARUH VARIASI KONSENTRASI BAHAN PENGISI DAN SUHU UDARA PENGERINGAN TERHADAP KUALITAS BUBUK JERUK NIPIS (Citrus aurantifolia) HASIL PENGERINGAN DENGAN SPRAY DRYER - , ANISA RATNA PRADANTI; , Dr. Joko Nugroho W.K., STP., M.Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Spray drying is a drying process that is commonly used for drying fluid or emulsion which is producing powders as a result. Spray drying process is usually used for non-durable-food preservation like lime fruit so it can prolong the limeâs shelf life. In lime juice drying with spray dryer, there are some main problems. The main problems in lime fruit juices preservation are the stickiness of lime fruit juices and low total solid that leads to no powder production. For preventing this problems, there are several ways and one of them is by adding carrier agents. Maltodextrin and CMC (carboxymethylcellulose) are the carrier agents that is usually used for fruit juice drying. This research is aimed for knowing the effect of inlet temperature and concentration of carrier agent in powdersâ quality. This research used spray dryer in pilot scale with pneumatic atomizer, 60-cm-diameters drying chamber, cyclone separator, and 10.000 watt of heater. This reaseacrch used two factors, there were variation of inlet temperature (190oC, 200oC, and 210oC) and variation of CMCâs concentration (0,1 %, 0,3%, and 0,5%) with two replication. 600 gr of lime juice will be flowed from feedstock to drying chamber with 2 bar of compressor preasure. Particle that is produced by the atomizer will be contacted by the hot air at 0,0066 m3/s. The result of this research showed that increasing the concentration of CMC will increase the viscosity of the lime juices and reduce the feed rate. The powdersâ moisture content were about 5,81 % - 7,15 %. Increasing concentration of CMC will increase the powdersâ moisture content but increasing the inlet temperature will reduce the powdersâ moisture content. Solubillity of the powder were at 79,5 % - 87,3 % and will increase as the increase of the inlet temperature and CMCâs concentration. Increasing the inlet temperature and CMCâs concentration will increase the degree of whiteness. Production eficiency of the process were at 27,96% - 52,05%. Keywords : Spray dryer, lime fruit, concentration of CMC, inlet temperature